Liposomal Bupivacaine Is Both Safe and Effective in Controlling Postoperative Pain After Spinal Surgery in Children: A Controlled Cohort Study. Issue 10 (December 2020) - Chughtai, Morad; Sultan, Assem A.; Hudson, Brittany; Goodwin, Ryan C.; Seif, John; Khlopas, Anton; Bena, James; Jin, Yuxuan; Gurd, David P.; Kuivila, Thomas E.; Ballock, Robert Tracy
Abstract : Study Design: Retrospective comparative cohort study. Objective: To evaluate: (1) pain relief efficacy; (2) opioid consumption; (3) length of stay (LOS); (4) discharge disposition (DD); and (5) safety and adverse effects of liposomal bupivacaine (LB) in pediatric patients who underwent spinal deformity correction. Summary of Background Data: LB is a long-acting, locally injectable anesthetic. Previous orthopedic studies investigating its use have been limited to adult patients. The use of LB as part of postoperative pain management in pediatric patients undergoing spine deformity correction surgery is yet to be evaluated. Materials and Methods: A total of 195 patients that received LB as part of their postoperative pain management regimen were compared with 128 patients who received standard pain management without LB. Pain intensity, opioid consumption, LOS, and DD were recorded. Potential LB-related complications were reported as frequencies and statistically compared for superiority. Noninferiority tests were performed using the Farrington-Manning score test. Multivariate tests based on generalized estimating equations were performed to determine the common and average treatment effects. Odds ratios (OR) with 95% confidence intervals (CI) were calculated. Results: The LB cohort demonstrated lower pain scores [postoperative day 1 (POD 1)—median=2, interquartile range (IQR)=(0–5) vs. 5 (2.5–7); POD 2—3 (0–5) vs. 4 (3–6); P <0.001], lower overall opioid consumption (78.2 vs. 129 morphine milligram equivalents; P =0.0001) and consistently from POD 0 to 3 (mean differences; 7.47, 9.04, 17.2, and 17.3 morphine milligram equivalents, respectively; P <0.01), shorter LOS (median=3 d, IQR=3–4 vs. 4 d, IQR=4–6; P <0.001), and similar to-home DD (98% vs. 97%). Complications were similar among the cohorts in superiority and 10% noninferiority analyses. Patients in the LB cohort had lower odds for complications (odds ratio=0.77; 95% CI, 0.64–0.93; P =0.009 and 0.67; 95% CI, 0.50–0.90; P =0.008). Conclusions: This study demonstrated the safety and efficacy of LB when added to the current multimodal postoperative pain management regimens after pediatric spinal surgery. Level of Evidence: Level III.